Innovation of Physics E-Module: Utilizing Local Wisdom of Lampung's Handwritten Batik in Teaching Heat and Temperature Material to Foster Students' Scientific Attitude - Sera Okta Pela; Nguyen Nhu Le; Peter Githae Kaboro; Ahmad Nurjamil (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The aim of this research is to investigate the implementation of a physics e-module based on the local wisdom of Lampung written batik in learning heat temperature material, with a focus on developing students' scientific attitudes. Methodology: The research method used is research and development (R&D). The instrument used in this research to measure students' scientific attitudes. This research will involve two classes, each of which will use a different learning approach. One class will use a conventional e-book while the other class will use an e-module developed based on the local wisdom of Lampung written batik Main Findings: The research results show that the use of this e-module is effective in improving students' scientific attitudes, such as curiosity, perseverance, and trust in scientific methods, which are important aspects in learning physics. By combining local traditions with modern scientific concepts, this approach not only enriches learning methods, but also strengthens students' cultural identity. Therefore, implementing physics e-modules based on local wisdom is a relevant strategy and has the potential to be applied in the context of physics learning in schools. Novelty/Originality of this research: The novelty of this research lies in the combination of modern technological approaches with local cultural values. In this research, the e-module was designed by considering the rich cultural context and traditions of Lampung batik, thereby creating a relevant and interesting learning experience for students.